2016
DOI: 10.1136/jmedgenet-2016-103883
|View full text |Cite
|
Sign up to set email alerts
|

GATOR1 complex: the common genetic actor in focal epilepsies

Abstract: The mammalian or mechanistic target of rapamycin (mTOR) signalling pathway has multiple roles in regulating physiology of the whole body and, particularly, the brain. Deregulation of mTOR signalling has been associated to various neurological conditions, including epilepsy. Mutations in genes encoding components of Gap Activity TOward Rags 1 (GATOR1) (DEPDC5, NPRL2 and NPRL3), a complex involved in the inhibition of the mTOR complex 1 (mTORC1), have been recently implicated in the pathogenesis of a wide spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
58
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 71 publications
3
58
1
1
Order By: Relevance
“…The fact that the same diseases are associated with loss of function mutations in GATOR1 12 and activating mutations in mTOR 21 , support the notion that KICSTOR is a negative regulator of the mTORC1 pathway. Consistent with the phenotypes of patients with mutations in KICSTOR components, the few mice deficient in Szt2 that survive to adulthood are more susceptible to epileptic seizures 20 .…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…The fact that the same diseases are associated with loss of function mutations in GATOR1 12 and activating mutations in mTOR 21 , support the notion that KICSTOR is a negative regulator of the mTORC1 pathway. Consistent with the phenotypes of patients with mutations in KICSTOR components, the few mice deficient in Szt2 that survive to adulthood are more susceptible to epileptic seizures 20 .…”
mentioning
confidence: 60%
“…Interestingly, several KICSTOR components are mutated in neurological diseases associated with mutations that lead to hyperactive mTORC1 signaling 510 . Thus, KICSTOR is a lysosome-associated negative regulator of mTORC1 signaling that, like GATOR1, is mutated in human disease 11,12 .…”
mentioning
confidence: 99%
“…PIK3CA), 7 Bannayan-Riley-Ruvalcaba syndrome (PTEN), 8 Tenorio syndrome (RNF125), 9 isolated hemimegalencephaly (PIK3CA and AKT3), 10 and with syndromes with epilepsy, hemimegalencephaly and/or FCD due to mutations in DEPDC5, NPRL2 and NPRL3 genes, involved in mTORC1 regulation. 11 Axial skeletal overgrowth is not affected by mutations in mTOR, but megalencephaly is clearly a finding. 12 The main differences between the syndromes involved in this pathway are based on: (1) its germinal or somatic origin, causing generalized or segmental distribution patterns as in hemi or megalencephaly, (2) the degree of mosaicism, and…”
Section: Introductionmentioning
confidence: 99%
“…The risk associated with these genes is mainly attributable to ultrarare variants (e.g., unseen in the large population variant databases 1000 genomes, Exome Variant Server [EVS] and Exome Aggregate Consortium [ExAC]), which is the same class of variants primarily implicated in the Mendelian forms. Ultrarare variants of DEPDC5 (DEP domain containing 5) are responsible for autosomal dominant focal epilepsies and recently were proposed as risk factors for complex epilepsies . Focal Epilepsies (FE), characterized by seizures originating within one cerebral hemisphere, are the most common epilepsy form accounting for 60%–70% of all the epilepsies .…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the two TSC complex subunit genes TSC1/TSC2 are traditionally linked to tuberous sclerosis, an autosomal dominant multisystemic disease characterized by cortical tubers in the brain and commonly associated with FE . It has been demonstrated that FE‐associated mutations in this group of genes cause hyperactivation of mTORC1 signaling, suggesting a common pathological mechanism with important implications for both patients’ treatment and prognosis . However, if considerable knowledge has been accumulated in the last years about centrality of the mTOR pathway in familial FE, it is far less clear to what extent its deregulation impacts isolated patients.…”
Section: Introductionmentioning
confidence: 99%